Kinetics and Energetics of Phylloquinone Reduction in Photosystem I: Insight From Modeling of the Site Directed Mutants - Santabarbara, Stefano; Casazza, Anna Paola (Frontiers in Plant Science, 2019)
Two phylloquinone molecules (A1), one being predominantly coordinated by PsaA subunit residues (A1A) the other by those of PsaB (A1B), act as intermediates in the two parallel electron transfer chains of Photosystem I. The oxidation kinetics of the two phyllosemiquinones by the iron-sulphur cluster FX differ by approximately one order of magnitude, with being oxidised in about 200 ns and in about 20 ns. These differences are generally explained in terms of asymmetries in the driving force for FX reduction on the two electron transfer chains. Site directed mutations of conserved amino acids composing the A1 binding site have been engineered on both reaction centre subunits, and proved to affect selectively the oxidation lifetime of either , for PsaA mutants, or , for PsaB mutants. The mutation effects are here critically reviewed, also by novel modelling simulations employing the tunnelling formalism to estimate the electron transfer rates. Three main classes of mutation effects are in particular addressed: i) those leading to an acceleration, ii) those leading to a moderated slowing (~ 5 folds), and iii) those leading to a severe slowing (>20 folds) of the kinetics. The effect of specific amino acid perturbations contributing to the poising of the phylloquinones redox potential and, in turn, to PSI functionality, is discussed.